Feasibility of Large Multi-Leaf Collimator in Stereotactic Radiosurgery/Stereotactic Radiotherapy: A Single Center Experience - Chaiyapong, Akanit; Watcharawipha, Anirut; Nobnop, Wannapha; Kongsa, Anupong; Jia-Mahasap, Bongkot (Biomedical Sciences and Clinical Medicine, 2024)
Objective This study investigated the feasibility of using a large multi- leaf collimator (MLC) in a C-arm based linear accelerator for stereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT). Methods Patient Specific Quality Assurance was conducted on 69 patients treated with a single lesion SRS/SRT measuring dose distribution using patient-specific plans with SRS MapCHECK®. Statistics were used to analyze the significance of correlation among dosimetric parameters, included Conformity Index (CI), Gradient Index (GI), plan complexity, and Gamma passing rate (GPR) in an absolute dose (AD) and relative dose (RD). confidence limit (CL) was also calculated to evaluate the performance of a large multileaf collimator (MLC) in SRS/SRT. Results Planning target volumes (PTVs) ranged between 0.34 cm3 and 30.42 cm3. The study found a value of CIICRU, CIPaddick, and GI of 1.29 ± 0.17, 0.77±0.10 and 5.24±2.18 (mean±SD), respectively, significant correlations were found between PTV sizes and dosimetric parameters. Values of GPR2%/2mm were 92.42±3.74 (AD), 96.38±3.24 (RD), whereas GPR2%/1mm were 82.03±6.69 (AD), 89.64±7.26 (RD). No significant correlation was found between plan complexity and GPR. CL values were 85.09% (AD), 90.03% (RD) for GPR2%/2mm and 68.92% (AD), 75.41% (RD) for GPR2%/1mm. Conclusions This study assessed the feasibility of using a large MLC for a single lesion SRS/SRT across various PTV sizes. The values of CI and GI decreased for a small lesion. While the large MLC performed adequately across different PTV sizes, the CL value of RD GPR at 2%/1 mm fell below 90%. This indicates that the contribution of PTV margin might be consi-dered for a large MLC in SRS/SRT